The impact of the Land Ceiling Act on Land and Housing Development in the Madras Metropolitan Area, and the introduction of the guided urban development scheme - Cherukuri, Sasidhar; Archer, Raymon W.; Kioe-Sheng, Yap; Robinson, Ira. M.; The Canadian International Development Agency (CIDA) under AIT-Canadian Universities Consortium Partnership Project (AIT-CUC-PP) (Bangkok : Asian Institute of Technology, 1990)
An effort was made to study the effects of the Urban Land (Ceiling and Regulation) Act, 1978 in the Madras Urban Agglomeration and more. specifically the Act's effects on the l and and housing system. It was found that this Act was a failure due to various reasons that include non-availability of cadester records, cumbersome procedures and uneconomical compensation offered. Simultaneously, this lead to (i) thriving unauthorised land subdivision activity within and beyond the ULCR Act zone; (ii) developers preferring to undertake apartment projects within the city rather than large land subdivision and housing projects; (iii) spill-over effect beyond ULCR Act zone. There was a general reluctance on the part of the landowners to dispose of their land and to undertake any initiatives to promote land and housing projects. The general failure of ULCR Act needed many corrective measures to encourage and involve landowners in land and housing development projects . With a package incentives the Guided Urban Development Scheme was formulated. Guided Urban Development Scheme was proposal conceived to encourage private developers and landowners undertake building low-cost residential units with necessary exemptions from the provisions of the Act. The incentives provided under GUO Scheme did not encourage the active participation of the developers and the landowners . The reason for this included : (i) lack of coordination between various agencies of the state; (ii) non-availability of infrastructure services; (iii) unpredictability of the government's motives; (iv) lack of adequate publicity for the scheme; and (v) the failure to process t he GUD applications submitted by the private developers in time. The private sector land and housing development is severely constricted due to ULCR Act and the threat of large-scale land acquisition. This led to unauthorised subdivision of urban land which were quite rampant, affecting every urban area . Based · on such a perception and understanding recommendations for planning are made that include scrapping of the ULCR Act and proper maintenance of cadestral records.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering
Thesis (M.Sc.) - Asian Institute of Technology, 1990
Keywords: Land use, Urban -- India -- Madras Metropolitan Area